2021
DOI: 10.1002/deo2.35
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of endoscopic resection for rectal neuroendocrine tumors: Advantages of endoscopic submucosal resection with a ligation device compared to conventional EMR and ESD

Abstract: Objectives There are some endoscopic resection (ER) methods for neuroendocrine tumors (NETs), however, which method is most useful remains unclear. This study aimed to compare the outcomes of different ER techniques, such as conventional endoscopic mucosal resection (cEMR), endoscopic submucosal dissection (ESD), and endoscopic submucosal resection with a ligation device (ESMR‐L) for rectal NETs. Methods We retrospectively analyzed 96 consecutive patients with 102 recta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
(139 reference statements)
0
7
0
Order By: Relevance
“…Some reports suggest that EMR with a ligation device (ESMR-L) may be the most useful ER method for NETs of less than 10 mm in diameter. 24 In view of the controversy over endoscopic resection of 10-20 mm R-NET, this study focused on the safety and efficacy of EMR and ESD treatments for R-NETs with a diameter ranging from 10 mm to 20 mm. We found that EMR and ESD resection exhibited lower complication rates for R-NETs measuring 10-20 mm in size.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggest that EMR with a ligation device (ESMR-L) may be the most useful ER method for NETs of less than 10 mm in diameter. 24 In view of the controversy over endoscopic resection of 10-20 mm R-NET, this study focused on the safety and efficacy of EMR and ESD treatments for R-NETs with a diameter ranging from 10 mm to 20 mm. We found that EMR and ESD resection exhibited lower complication rates for R-NETs measuring 10-20 mm in size.…”
Section: Discussionmentioning
confidence: 99%
“… 35 In another study measuring vertical margin distances from the tumor, EMR-L had a higher complete resection rate than ESD (100% vs. 85.7%) and a more distant vertical margin from the tumor in the EMR-L group than in the ESD group (vertical margin distance, 641.5±763.8 vs. 202.8±125.4 μm, EMR-L vs. ESD). 48 In a study comparing the clinical outcomes of EMR-L and EMR-C, the endoscopic en bloc resection rate was higher in the EMR-L group (100% vs. 92.9%, p =0.003), although the complete resection rate was similar (92.5% vs. 83.3%, p =0.087, respectively). 7 The reason EMR-L has a higher complete resection rate than EMR-C is that when using a band, lateral and deep margins are more easily secured in EMR, where EMR-L uses a technique that resects the tumor by snaring below the band ligation.…”
Section: Which Methods Is Best?mentioning
confidence: 98%
“…Data comparing different endoscopic methods used for the management of rectal NETs, including complete resection rates and complications, are presented in Table 3. 7,[27][28][29][30][31][35][36][37][38][39][40][41][42][44][45][46][47][48] Various factors should be considered to determine which method is better. Although a method with a high histologic complete resection rate is mandatory, the complication rate, status of the equipment in the hospital, proficiency of the therapeutic endoscopists and assistants, short procedure time, and length of hospital stay should be considered.…”
Section: Which Methods Is Best?mentioning
confidence: 99%
“…A high R0 resection rate is reportedly achieved for colorectal NETs with ESD; however, it is necessary to remember that dissection at a slightly superficial level can easily result in a positive vertical resection margin 13,19 . In fact, several studies have demonstrated the superiority of modified EMR to ESD in terms of R0 resection 19,26,27 . Dissection at a sufficiently deep layer (just above the muscularis layer) is essential for achieving R0 resection for colorectal NETs with ESD (Figure 2).…”
Section: Procedures Of Endoscopic Resection For Colorectal Netmentioning
confidence: 99%